A Massive Ovarian Mucinous Cystadenoma: A Rare Case Report (Delta Medical College Journal, 2015)
Ovarian mucinous cystadenoma is a benign tumour that arises from the surface epithelium of the ovary. It tends to be huge in size if not detected early. We describe a 32 year old woman (para 1+0) presented with marked abdominal distension, discomfort and vague pain in the abdomen with dyspepsia, anorexia, nausea, vomiting and irregular menstruation for last three months with the suspicion of pregnancy. On examination no findings were in favour of pregnancy, rather an ill defined abdominal mass about 30 weeks pregnancy size was found. Transabdominal USG revealed a big multiloculated ovarian cyst of about 25x20 cm. On laparotomy a huge cystic mass was noticed arising from left ovary. The cyst wall was smooth, intact and without any external projection though adherent with the left fallopian tube and left salpingo-oophorectomy was done. Histopathological examination revealed an ovarian cyst compatible with mucinous cystadenoma. Such giant ovarian tumours have become rare in current practice. This case report emphasizes the significance of thorough evaluation of all women presented with non specific complaints like vague abdominal pain or simple dyspepsia. Although the condition is rare, it is potentially dangerous in the massive form if not timely diagnosed and managed properly. With the increasing awareness of such conditions, more and more cases could be detected and reported early. DOI: http://dx.doi.org/10.3329/dmcj.v3i1.22239 Delta Med Col J. Jan 2015; 3(1): 48-51